BUSINESS ACTORS' RESPONSIBILITY FOR CONSUMER LOSSES DUE TO NAIL GEL IN SALON BUSINESSES IN BADUNG REGENCY - Desak Gde Dwi Arini; Ni Gusti Ketut Sri Astiti; I Kadek Ari Putra (Adisam Publisher, 2026)
Nail gel services in salon businesses in Badung Regency are a form of beauty service that uses certain chemicals and techniques, requiring adequate consumer protection and business actor accountability. This study focuses on how business actors are held accountable for losses suffered by nail gel consumers in salons in Badung Regency and how dispute resolution models for these losses occur. The method used is an empirical legal approach through research using interviews and direct field observations. The results of the study indicate that business actors' liability for losses suffered by nail gel consumers in salons in Badung Regency has not been implemented optimally, particularly in terms of providing risk information and ensuring the mechanism for liability models for losses suffered by nail gel consumers. Legal provisions related to nail gel consumer protection in Badung Regency are already available, including the Consumer Protection Law (UUPK), the Civil Code, and health and cosmetics regulations. Dispute resolution is generally conducted through deliberation using a family approach, but this mechanism remains informal and therefore does not provide strong legal certainty. This study emphasizes the need for improved service standards, information transparency, and more structured complaint handling procedures to strengthen consumer protection in nail gel consumer services at salons in Badung Regency.